Influence of Microscopically Positive Resection Margins on Long-Term (>5-Year) Survival after Resection of Pancreatic Ductal Adenocarcinoma - Hamada, Yoshihiro; Maeshiro, Kensei; Nakayama, Yoshifuku (JOP. Journal of the Pancreas, 2014)
Context The impact of R1 resection on outcomes in patients with pancreatic ductal adenocarcinoma (PDAC) is unclear, with most studies assessing survival for up to 5 years. Objective The aim of this study was to evaluate the prognostic influence of R1 and R0 resection on >5-year survival in patients with PDAC. Material and methods Of the 271 patients with PDAC who underwent pancreatic resection over a 26-year period, 33 had survived for ≥5 years. R1 status was defined as the presence of tumor tissue ≤1 mm from a circumferential margin surface. Patients were followed-up for 61 to 288 months. Results Of the 33 long-term survivors, 19 and 14 underwent R0 and R1 resection, respectively. The percentage of male patients was significantly higher in the R1 than in the R0 group. The R0 group tended to show a weaker relationship between R status and stage than the R1 group. Multivariate analysis showed that R status was an independent prognostic marker (P=0.0071), and Kaplan–Meier curves showed that >5-year survivors in the R1 group had significantly poorer prognoses (P=0.002). Conclusions Patients who have survived >5 years following R1 resection for PDAC can experience tumor recurrence in the resected area. Image: Kaplan–Meier survival curves of patients with PDAC.